The Form and Meaning of Bima Deep Weaving Motif Culture in Bima Community of West Nusa Tenggara - Irfan Hidayat; Risyaf Kudus Pranasa (Jurnal Ilmu Sosial dan Humaniora, 2023)
Study This aim for know and describe about cloth weaving typical West Nusa Tenggara Bima area includes (1) history existence Bima weaving, and (2) form and meaning of the motifs on the cloth weaving typical Bima area. Study This use method descriptive qualitative, instrument in study This is researcher. For strengthening research, researcher use guidelines observation, interview, and documentation. object study This is culture Rimpu in Bima district. Data validation is done with adequacy referential and persistence observation. Whereas technique deep data analysis study This is descriptive qualitative and use stages that is data collection, data presentation, and withdrawal conclusion. Based on results weaving motif research culture the Bima community of West Nusa Tenggara, namely: (1) Based on customary provisions, every woman who enters her teens must be skilled at doing Muna ro Medi, which is an activity of mothers to improve the welfare of family life. These customary orders were obeyed by all Mbojo women until the 1960s. From an early age, girls are guided and trained to become “Ma Loa Ro Tingi” (skillful and artistic) weavers. (2) Weaving Bima has four basic motives namely floral motifs samobo Which meaning A hope society, flower satako who became symbol personality somebody like sprig spreading flowers fragrant and beautiful in her life, flower kakado who have cue that position highest and top namely the Lord of the Universe Nature and flowers aruna Which contain the meaning of the 99 attributes of God, as creator always nature praised and worshiped by His servants.